Kairos revisited : investigating the relevance of the Kairos document for church-state relations within a democratic South Africa - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.